The Application of Polycaprolactone in Three-Dimensional Printing Scaffolds for Bone Tissue Engineering - Yang, Xiangjun; Wang, Yuting; Zhou, Ying; Chen, Junyu; Wan, Qianbing (Polymers, 2021)
Bone tissue engineering commonly encompasses the use of three-dimensional (3D) scaffolds to provide a suitable microenvironment for the propagation of cells to regenerate damaged tissues or organs. 3D printing technology has been extensively applied to allow direct 3D scaffolds manufacturing. Polycaprolactone (PCL) has been widely used in the fabrication of 3D scaffolds in the field of bone tissue engineering due to its advantages such as good biocompatibility, slow degradation rate, the less acidic breakdown products in comparison to other polyesters, and the potential for loadbearing applications. PCL can be blended with a variety of polymers and hydrogels to improve its properties or to introduce new PCL-based composites. This paper describes the PCL used in developing state of the art of scaffolds for bone tissue engineering. In this review, we provide an overview of the 3D printing techniques for the fabrication of PCL-based composite scaffolds and recent studies on applications in different clinical situations. For instance, PCL-based composite scaffolds were used as an implant surgical guide in dental treatment. Furthermore, future trend and potential clinical translations will be discussed.